Output-Based Aid in Telecommunications : New Models for Universal Access in Latin America - Muente, Arturo Kunigami (World Bank, Washington, DC, 2012)
During the 1990s many Latin American countries developed universal access programs, financed through universal service funds, to increase telecommunications access in rural and low-income areas. The mechanism most often used to allocate the funds was the minimum subsidy tender, with subsidy payments linked to predefined performance criteria (such as installation of telephones in rural areas) under an output-based aid (OBA) approach. After more than 10 years' experience, a study evaluated the performance of the universal service funds in Latin America, home to some of the first OBA programs in telecommunications. The aim was to identify lessons and best practices and help regulators define a new generation of universal access programs using OBA mechanisms.